Heart rate variability in patients with anxiety disorders: A systematic review and meta‐analysis - Cheng, Ying‐Chih; Su, Min‐I; Liu, Cheng‐Wei; Huang, Yu‐Chen; Huang, Wei‐Lieh (Psychiatry and clinical neurosciences, 2022)
Aims Patients with anxiety disorders (AD) have been found to have lower heart rate variability (HRV) than healthy individuals in some studies, but this was inconsistent. Furthermore, the influence of distinct diagnoses, study design, and demographic factors on the results was not comprehensively examined. Methods We gathered studies comparing HRV in patients with AD and in healthy controls. The parasympathetic activity in the hierarchical order principle was adopted in the main analysis. We adopted the random effects model to calculate the standardized mean difference. Results Of the 7805 screened studies, 99 were included in the quantitative analysis, with a total of 4897 AD patients and 5559 controls finally entered the meta‐analysis. AD patients had a significantly lower resting‐state HRV for parasympathetic activity compared to control (Hedges' g = −0.3897). For the diagnostic subgroup analysis relative to the controls, resting‐state HRV was significantly lower in post‐traumatic stress disorder, panic disorder, generalized anxiety disorder, and social anxiety disorder patients. HRV reactivity (all reactivity data, data on physiological challenge, and psychological challenge) did not show significant inter‐group differences between AD patients and healthy subjects. Conclusions The results supported that patients with AD had significantly lower resting‐state HRV than the healthy population, but no alterations were found for HRV reactivity.